Molecular diagnostic of complicated pneumonia in the post-vaccine era. (13th October 2022) - de Vasconcelos, Mariana Galvão Gurgel Cabral; Jarovsky, Daniel; Nunes, Gabriela Zembruski; Tridente, Daniela Marinho; Grill, Juliana Amorim Teixeira; Berezin, Eitan Naaman
SUMMARY: Background: The etiological diagnosis of community-acquired pneumonia (CAP) is still a challenge. We compared the conventional culture method and real-time polymerase chain reaction (RT-PCR) for the identification of Streptococcus pneumoniae in severe pediatric CAP. Methods: A retrospective hospital-based study was conducted. From 2012 to 2018, we have selected patients who had peripheral blood and/or pleural fluid collected for etiological investigation by RT-PCR. Results: We included 113 children (median age: 3 years; interquartile range 1–6 years). RT-PCR increased the detection rate of S. pneumoniae by 6.5 times using blood samples and eight times using pleural fluid samples. Patients subjected to RT-PCR showed more prolonged hospitalization ( p = 0.006), fewer comorbidities ( p = 0.03), presence of pleural effusion ( p = 0.001), presence of young forms of leukocytes ( p = 0.001) and radiograph with characteristics of pneumonia ( p = 0.002). The presence of pleural effusion [odds ratio (OR) = 14.7, 95% confidence interval (CI) 1.6–133.9; p = 0.01] and young forms of leukocytes (OR = 8.9, 95% CI 0.9–84.4; p = 0.05) were risk factors for positive RT-PCR pneumococcal when multivariate analysis was performed. Conclusions: RT-PCR is a reliable method for diagnosing severe CAP using sterile materials and a potentially applicable method in patients with clinical, radiological and non-specific laboratory characteristics of lower respiratory tract infection, especially in complicated cases with pleural effusion.